(untitled) (Journal of Economic Research & Business Administration, 2019)
The article presents an analysis of the innovation activities of the regions of the Republic of Kazakhstan, identifies the reasons that impede the formation of the innovation environment, in which the components of growth of regional competitiveness are still poorly developed. General approaches to the formation of the term “innovative environment” are analyzed. The authors of the article noted that the solution to the problem of forming an effective innovation environment lies in two interrelated planes, caused, firstly, by the need to create external conditions conducive to innovation development, which include a combination of institutions and organizations in the structure of national innovation systems. Secondly, the presence of objective prerequisites for the transition to an innovative development path for business entities. Particular attention is also paid to the use of competitive advantages of the regions of Kazakhstan. The authors suggested ways to create an effective innovation environment and improve the innovation partnership of all participants: the state, business, science and education. In assessing the innovation activity of the regions of the Republic of Kazakhstan, these indicators were used: expenditures on research and development, expenditures on technological innovations, output of innovative products per person in the region, etc., based on the results of the research a SWOT analysis was conducted, a model of innovative development of the enterprise was proposed, where the general strategic goals of the enterprise and the main directions of innovative development would be agreed.